The Wartime Labor Force in Major Industrial Areas - Goldfield, Edwin D. (The Review of Economics and Statistics, 1945)
ONE of the most troublesome statistical I shortcomings at the outset of World War II was the lack of pertinent data on the behavior of the labor force under conditions of exaggerated demand. The exertions of the last war had been of much lesser magnitude; moreover, they had been inadequately and imperfectly recorded. There was little to serve as a guide in appraising manpower resources or in determining the most fruitful and feasible channeling of pressure and persuasion. The statistical record of this war will be much more complete. Not only are we better supplied with current information on the development of the nation's wartime labor force, but we also have become more fully aware of the necessity of attacking our manpower problems on an area basis. The geographical distribution of the stresses and strains accompanying the war effort has been far from uniform. An appreciation of the extent to which the population has met the increased demands, through mobility of workers and through the recruiting of persons who normally would not work, and of the practical limits of the expansibility of the labor force may be obtained in part by an analysis of some of the boom areas in which war production has been concentrated. In the spring of I944 the Bureau of the Census, in cooperation with the President's Committee for Congested Production Areas, conducted a census of ten boom areas, to secure data about the wartime population.' This census yielded information on the size of the labor force, the relative contributions of the various population groups to each area's labor supply, the part played by migrant workers, the length of the work-week, and other significant items. When compared with the benchmarks provided by the Decennial Census of Population four years previously, just before the beginning of the defense boom, these data furnish a graphic description of the dynamics of labor supply in wartime.2 Each of the designated areas was so defined as to include not only the center of industrial activity but also the surrounding territory in which many of the workers and their families live and in which many large new war plants have been built. Each area comprises a county or a group of contiguous counties, embracing a critical war production center. The areas and the counties which they comprise are as follows: